Edukasi Pencegahan dan Pengendalian Diabetes Melitus - Nur Wahyuni Munir; Safruddin Safruddin; Andi Yuliana (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2023)
Diabetes Mellitus (DM) is a multisystem chronic disease associated with abnormal insulin production, impaired insulin use, or both. Education about DM aims to increase knowledge as an effort to prevent DM. Educational material about understanding, signs and symptoms, blood glucose test values, and efforts to prevent DM. The methods used are lectures and discussions. The media used are leaflets, banners, pretest and posttest questions. The results of this community service activity showed an increase in knowledge in the good category by 42% before and after counseling was carried out. It is recommended for the next service in the community so that they can demonstrate directly how to process traditional medicines for dyspepsia.Â Keywords: Diabetes mellitus; Prevention; Control: Blood glucose